Economic incentives and natural resource management among small-scale farmers: Addressing the missing link - Getnet, Kindie; Pfeifer, Catherine; MacAlister, C. (Elsevier, 2014)
Small-scale farmers face numerous challenges to invest in natural resource management practices. The problems are interlinked, with such perverse economic problems as high transaction costs and risk rooted in the lack of comprehensive institutional and organizational services to farmers for risk reduction and incentive creation. Failure to address such a missing link undermines success in natural resource management. This paper ponders the importance of such a missing link and proposes analytic framework that explicitly integrates the economics of natural resource management into institutional and organizational analysis. The framework features the instrumentality of integrated institutional and organizational innovation to create opportunities and incentives to small-scale farmers to encourage investment in natural resource management practices.